Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get quick and reliable solutions to your questions from a community of seasoned experts on our user-friendly platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
The solution of x in -6 + 3x - 9x^2 = -16 is [tex]x = \frac{3 \pm \sqrt{369}}{18}[/tex]
How to solve the equation?
The equation is given as:
-6 + 3x - 9x^2 = -16
Add 16 to both sides
10 + 3x - 9x^2 = 0
Rewrite as:
9x^2 - 3x - 10 = 0
Solve for x using the quadratic formula
[tex]x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}[/tex]
So, we have:
[tex]x = \frac{3 \pm \sqrt{(-3)^2 - 4 * 9 * -10}}{2 * 9}[/tex]
Evaluate
[tex]x = \frac{3 \pm \sqrt{369}}{18}[/tex]
Hence, the solution of x in -6 + 3x - 9x^2 = -16 is [tex]x = \frac{3 \pm \sqrt{369}}{18}[/tex]
Read more about quadratic functions at:
https://brainly.com/question/1497716
#SPJ1
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.